The Trend of Direct Medical Cost of Meliodiosis Patients in Kedah: A Retrospective Study from 2014 to 2017 - Mardhiah K; Wan-Arfah N; Naing NN; Abu Hassan MR; Chan HK; Hasan H (Dove Medical Press, 2021)
Kamaruddin Mardhiah,1,2 Nadiah Wan-Arfah,2 Nyi Nyi Naing,3 Muhammad Radzi Abu Hassan,4 Huan-Keat Chan,4 Hazriah Hasan1 1Faculty of Entrepreneurship and Business, Universiti Malaysia Kelantan, Kota Bharu, Kelantan, Malaysia; 2Faculty of Health Sciences, Universiti Sultan Zainal Abidin, Kuala Terengganu, Terengganu, Malaysia; 3Faculty of Medicine, Universiti Sultan Zainal Abidin, Kuala Terengganu, Terengganu, Malaysia; 4Clinical Research Center, Hospital Sultanah Bahiyah, Ministry of Health Malaysia, Alor Setar, Kedah, MalaysiaCorrespondence: Nadiah Wan-ArfahFaculty of Health Sciences, Universiti Sultan Zainal Abidin, Gong Badak Campus, Kuala Nerus, Kuala Terengganu, Terengganu, 21300, MalaysiaTel +6012-6260508Email wanwaj@unisza.edu.myPurpose: This study was conducted to determine the direct medical cost of treating melioidosis patients. The calculation was made according to the variables extracted from medical records.Materials and Methods: Data collection was performed retrospectively on a total of 293 cases from Hospital Sultanah Bahiyah, Kedah, Malaysia. The data consisted of personal information, treatment history, and investigation findings, including blood results, USG abdomen results, and CT scan results. The site of culture and sensitivity were also obtained. The total direct medical cost was based on the antibiotics/treatments received by the patients, diagnostic test and investigations performed. The trend analysis used to see the pattern of costs from 2014 to 2017. All the costs were compared based on patients’ status and duration of stay at the hospital using the independent t-test.Results: The overall mean of direct medical cost for melioidosis amounted to US $233.61 (RM931.33). Overall, the finding confirms a huge reduction (44.7%) of direct medical cost from 2014 to 2017 (P = 0.001). From 2015 to 2016, there was a 19.1% reduction of direct medical cost (P> 0.95), followed by a 38.8% reduction in costs from 2016 to 2017 (P = 0.019). In the case of the duration of stay, the mean of total direct medical cost among patients with ≥ 14 duration of stay was higher compared to those with < 14 duration of stay (p < 0.001). There was no significant mean difference of direct medical cost between patients who were cured and died.Conclusion: Despite the higher mortality of melioidosis cases compared to other infectious diseases, there is a limitation in the amount of published data on the management cost of melioidosis. The importance of cost in managing this disease should be underlined to perform a fully prepared management toward the disease.Keywords: melioidosis, direct medical cost, trend analysis